A Bioenergetic Clinical Case Study of Sarah - Rhoads, D. Emma (Bioenergetic Analysis, 2022)
This is a case study written as the final paper for my clinical training program at the New York Society for Bioenergetic Analysis. Our final year of training was focused on the study of transference and countertransference dynamics. The assignment for this paper was to present a case study including a clinical formulation of the characterological dynamics of the client’s personality functioning, a bioenergetic body and character assessment, and an examination of the transference and countertransference dynamics within the treatment.